THE EFFECT OF WORK DISCIPLINE, COMPETENCE, AND REWARDS ON EMPLOYEE PERFORMANCE AT BANK BCA KFPT BATAM - Aprilia Puspita Sari; Sabri; Sumardin (CV. Radja Publika, 2026)
This study aims to analyze the effect of Work Discipline, Competence, and Reward on Employee Performance at Bank BCA KFPT Batam. This research employs a quantitative method with an associative approach. The population consisted of 198 employees, and the sample was determined using the Slovin formula with a 10% margin of error, resulting in 66 respondents. The sampling technique used was Simple Random Sampling. Data analysis was conducted using multiple linear regression with the assistance of SPSS software.The validity test results indicated that all questionnaire items were valid, with r-count values greater than 0.244 and significance values less than 0.05. The reliability test showed that all variables were reliable, with Cronbach's Alpha values greater than 0.60 (Work Discipline = 0.876; Competence = 0.859; Reward= 0.827; Employee Performance = 0.873). The classical assumption tests demonstrated that the data were normally distributed (Sig. 0.078 > 0.05), with no multicollinearity (Tolerance > 0.10 and VIF < 10) and no heteroscedasticity.Simultaneously, Work Discipline, Competence, and Reward had a significant effect on Employee Performance, with an F-value of 29.703 > 2.75 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) was 0.590, indicating that 59.0% of the variation in Employee Performance could be explained by the three independent variables, while the remaining 41.0% was influenced by other factors not examined in this study.